Separating cationic and anionic redox activity in the lithium-rich antiperovskite (Li2Fe) SO - Singer, Lennart; Dong, Bowen; Mohamed, Mohamed A. A.; Carstens, Frederik; Hampel, Silke; Gräβler, Nico; Klingeler, Rüdiger (ACS applied materials & interfaces, 2024)
Lithium-rich antiperovskites promise to be a compelling class of high-capacity cathode materials due to the existence of both cationic and anionic redox activity. Little is however known about the effect of separating the electrochemical cationic process from the anionic process and the associated implications on the electrochemical performance. In this context, we report the electrochemical properties of the illustrative example of three different (Li2Fe)SO materials with a focus on separating cationic from anionic effects. With the high-voltage anionic process, an astonishing electrochemical capacity of around 400 mAh g-1 can initially be reached. Our results however identify the anionic process as the cause of poor cycling stability and demonstrate that the fading reported in previous literature is avoided by restricting to only the cationic processes. Following this path, our (Li2Fe)SO-BM500 shows strongly improved performance as indicated by constant electrochemical cycling over 100 cycles at a capacity of around 175 mAh g-1 at 1 C. Our approach also allows us to investigate the electrochemical performance of the bare antiperovskite phase excluding extrinsic activity from initial or cycling-induced impurity phases. Our results underscore that synthesis conditions are a critical determinant of electrochemical performance in lithium-rich antiperovskites, especially with regard to the amount of electrochemical secondary phases, while the particle size has not been found to be a crucial parameter. Overall, separating and understanding the effects of the cationic from the anionic redox activity in lithium-rich antiperovskites provides the route to further improve their performance in electrochemical energy storage.
Im Titel ist die "2" bei Li2Fe tiefgestellt
Gesehen am 14.01.2025